Differences in the Frequency of Use of Epidural Analgesia between Immigrant Women of Turkish Origin and Non-Immigrant Women in Germany – Explanatory Approaches and Conclusions of a Qualitative Study - Petruschke, I.; Ramsauer, B.; Borde, T.; David, M. (Geburtshilfe und Frauenheilkunde, 2016)
Introduction: The starting point of this study was the considerably lower rate of epidural analgesia use among women of Turkish origin in Germany compared to non-immigrant women in the German Research Foundation (DFG)-funded study entitled “Perinatal Health and Migration Berlin”. The study aimed to identify possible differences in the womenʼs attitudes towards epidural analgesia.Methods: Exploratory study with semi-structured interviews, interviews lasting 17 minutes on average were conducted with 19 women of Turkish origin and 11 non-immigrant women at a Berlin hospital. The interviews were subjected to a qualitative content analysis.Results: Immigrant women of Turkish origin in Germany more frequently ascribe meaning to the pain associated with vaginal delivery. They more frequently categorically reject the use of epidural analgesia, 1) for fear of long-term complications such as paralysis and back pain and 2) based on the view that vaginal delivery with epidural analgesia is not natural. Information on epidural analgesia is frequently obtained from a variety of sources from their social setting, in particular, by word of mouth. The women in both groups stated that they would take the decision to use epidural analgesia independent of their partnerʼs opinion.Discussion: The differences in epidural analgesia use rates observed correspond to the womenʼs attitudes. For the immigrant women of Turkish origin in Germany, the attitude towards using epidural analgesia is based in part on misinformation. In order to enable the women to make an informed decision, epidural analgesia could receive a stronger focus during childbirth courses.
Keywords: birth; pregnancy; delivery; pain; labour; labour pain